Accuracy of Intraocular Lens Power Calculation Using Anterior Chamber Depth from Two Devices with Barrett Universal II Formula - Hannah Muniz Castro; Audrey X. Tai; Samuel J. Sampson; Matthew Wade; Marjan Farid; Sumit Garg (Journal of Ophthalmology)
Purpose. To compare the preoperative measurements of the anterior chamber depth (ACD) by the IOLMaster and Catalys; additionally, to compare the accuracy of the IOL power calculated by the Barrett Universal II formula using the two different measurements. Setting. University of California, Irvine, Gavin Herbert Eye Institute in Irvine, California. Design. Retrospective comparative study. Methods. This study included 144 eyes of 90 patients with a mean age of 72.0 years (range 40.8 to 92.1 years) that underwent femtosecond laser-assisted cataract surgery using Catalys. Preoperative measurements of ACD were taken by the IOLMaster and Catalys. Manifest refraction and refractive spherical equivalent were measured 1 month postoperatively. Expected refractive results were compared with actual postoperative refractive results. Results. The correlation between the ACD values from the two devices was good (r = 0.80). The Catalys ACD measurements yielded a larger ACD compared to the IOLMaster, with a mean difference of 0.22 mm (P<0.0001). The correlation between the postoperative and predicted RSE of the implanted IOL power was excellent (r = 0.96). There was no statistically significant difference between the mean absolute error derived from the IOLMaster, 0.37 diopter (D) ± 0.34 (SD), and the Catalys, 0.37 ± 0.35 D (P=0.50). Conclusions. The Catalys biometry yielded a significantly larger ACD value than the IOLMaster. This difference in ACD value, however, did not reflect in a statistically significant difference in IOL power calculation and refractive prediction error using the Barrett Universal II Formula.